Pengaruh komunikasi dan motivasi terhadap kinerja pegawai - Didi Wandi (Amal Insani Foundation, 2022)
This study aims to determine and analyze the effect of communication and motivation on employee performance. This research uses descriptive analytical research with a qualitative approach. The method used in this research is a survey method. Respondents in this study were some of the employees of the BPBD of Serang Regency, which amounted to 76 people. The measuring instrument used in this research is a questionnaire. Analysis of the data used is a regression test using the SPSS version 25 program. The results of hypothesis testing that have been formulated show that both partially and simultaneous communication and motivation have a significant effect on employee performance in the field of emergency handling of BPBD Serang Regency.